Physical and mechanical properties of injection molded co-cr-mo alloy powder for orthopedic applications - Johari, Nurhaslina; Sauti, Rosliza; Abdullah, Noorsyakirah; Mohd Zainon, Nurazilah; Meh, Bakar; Abd Jalil, Mohd Nizam; Mohd Hijazi, Mohd Bakri; Omar, Ahmad Zahid; Omar, Mohd Afian; Baharuddin, Mohd Yusof; Zulkifly, Ahmad Hafiz (Trans Tech Publications Ltd., Switzerland, 2016)
Cobalt-chromium alloys are commonly used for surgical implants because of their high strength, superior corrosion resistance, non-magnetic behavior, and biocompatibility. Cobalt- Chromium-Molybdenum (Co-Cr-Mo) applications include prosthetic replacements of hips. This paper presents the attempt to produce metallic implant using Co-Cr-Mo powder by MIM process, focusing on the effects of different heating rate during sintering process at 1380 oC. Co-Cr-Mo powder was mixed homogeneously with palm oil based binder with powder loading of 65 vol% and was injection molded using vertical injection molding machine with the nozzle temperature of 160 °C to produce green compacts. The binders were then removed by solvent extraction process and sintered in vacuum condition at 10-5 mbar at 1380 °C. Results indicated that sintered density and tensile strength varies from 8.1 g/cm3 to 8.2 g/cm3 and 546 MPa to 797 MPa respectively. The mechanical properties comply with the international standard (ASTM F75).